Antonio bandeira trajano and the pedagogical renewal read in schoolbooks: Teach arithmetic intuitively (late nineteenth century) - Oliveira, Marcus Aldenisson [UNESP] (FapUNIFESP (SciELO), 2019)
This article presents results of researches that were developed from the scientific initiation to the doctorate. While traveling through so many possible paths of research, I always feel drawn to the topic of intuitive teaching of Arithmetic in primary schools during the late nineteenth century. Taking the arithmetic trilogy of Antonio Bandeira Trajano - Aritmética Primária, Aritmética elementar ilustrada e Aritmética progressiva -, for analysis, I came to clear evidence that Brazil appropriated not only a pedagogical model of the United States - the intuitive teaching of Arithmetic -, but also a graphic-editorial model of a school book. In addition, the three works analyzed here are witnesses of the first attempts to constitute an Arithmetic pedagogy in Brazilian primary schools, which I have called practical-intuitive pedagogy.
Antonio bandeira trajano e a renovação pedagógica lida em livros escolares: Ensinar aritmética de modo intuitivo (final do século xix)
Keywords: Antonio Bandeira Trajano; Arithmetic; Intuitive method; Practical-intuitive pedagogy; Schoolbook